The Hybrid Effect of Jute/Kenaf/E-Glass Woven Fabric Epoxy Composites for Medium Load Applications: Impact, Inter-Laminar Strength, and Failure Surface Characterization. Issue 4 (19th May 2019) - Sanjay, M. R.; Arpitha, G. R.; Senthamaraikannan, P.; Kathiresan, M.; Saibalaji, M. A.; Yogesha, B.
ABSTRACT: This research has been carried out to find better hybrid natural/glass fiber-reinforced composites for engineering applications. This research work studied the impact and inter-laminar strength of E-glass with jute/kenaf woven fabric epoxy composites with the aim of evaluating the hybridization effects on different laminate stacking sequences made with jute, kenaf, and E-glass fabrics by the vacuum bagging method. All the laminates were prepared in 300 × 300 mm 2 with a total of five plies maintained at 3 mm thickness, by varying the number and position of jute, kenaf, glass layers so as to obtain nine different stacking sequences. Among them, one group of all pure jute, pure kenaf, and pure E-glass laminates were also fabricated for comparison purpose. The specimen preparation and testing were carried out as per ASTM standards. From the results, it is shown that the properties of jute/kenaf fabrics-reinforced epoxy composites can be enhanced by hybridization with the addition of glass fabrics. The hybridization of jute/kenaf fabrics with E-glass fabrics provides a method to improve the mechanical impact and inter-laminar strength over pure natural fiber-reinforced composites. The hybrid laminate having E-glass and kenaf fiber plies as skin layers and jute fiber plies as core layers showed better properties compared to other laminates.